2023
DOI: 10.2174/1871527321666220222092655
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles as Powerful Tools for Crossing the Blood-brain Barrier

Abstract: The blood-brain barrier (BBB) is considered an important protective barrier in the central nervous system (CNS). The barrier is mainly formed by endothelial cells (ECs) interconnected by various junctions such as tight junctions (TJs), gap junctions, and adherent junctions. They collectively constitute an intensive barrier to the transit of different substances into the brain, selectively permitting small molecules to pass through by passive movement but holding off large ones such as peptides and proteins to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…[6] Blood barrier disruption is an important stimulator on the development of Parkinson disease. [7] Blood brain barrier dysruptions vascular inflammation are observed in the basal ganglia in Parkinson's disease. [16,17] Magnetic resonance images detected atrophy in gray matter, amygdala, hippocampus and basal ganglia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6] Blood barrier disruption is an important stimulator on the development of Parkinson disease. [7] Blood brain barrier dysruptions vascular inflammation are observed in the basal ganglia in Parkinson's disease. [16,17] Magnetic resonance images detected atrophy in gray matter, amygdala, hippocampus and basal ganglia.…”
Section: Discussionmentioning
confidence: 99%
“…[24] What Our Study Suggests About the Etiology of Parkinson's Disease It is now certain that cerebral icemias disrupt the bloodbrain barrier. [7] If so; disruption of the blood-brain barrier as well as the collapse of the intelligence, military and civil defense systems of the brain; it means that it has become vulnerable to internal and external attacks. The blood flow of subthalamic nucleus is maintained by the perforforant branches of middle cerebral artery, posterior cerebral artery and anterior cerebral arteries in rats in order from most to least.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proved that QDs were able to cross the blood–brain barrier and entered the central nervous system. 127 In addition, it was found that QDs are mainly transported from nose to brain through olfaction and transported through axons. 128 …”
Section: In Vivo Toxicity Of Qdsmentioning
confidence: 99%
“…Drugs that target AD or PD are needed to deliver across the blood-brain barrier (BBB) [ 11 , 12 ], which prevents 98% of neuropharmaceuticals from accessing the brain [ 13 ]. BBB contains brain capillary endothelial cells connected through tight junctions, which restricts paracellular transport and prevents the brain from harmful stimuli [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%